The Perception of Deceptive Information Can Be Enhanced by Training That Removes Superficial Visual Information - Ryu, Donghyun; Abernethy, Bruce; Park, So Hyun; Mann, David L. (Frontiers in Psychology, 2018)
The ability to detect deceptive intent within actions is a crucial element of skill across many tasks. Evidence suggests that deceptive actions may rely on the use of superficial visual information to hide the basic kinematic information which specifies the actor’s intent. The purpose of this study was to determine whether the ability of observers to anticipate deceptive actions could be enhanced by training which removes superficial visual information. Novice badminton players (n = 36) were allocated to one of three groups, who performed perceptual training over three days, with the efficacy of training assessed using tests of anticipatory skill conducted at pre-test, post-test, and a 1-week retention test. During training, participants watched a series of non-deceptive badminton shots performed by actors, with the footage manipulated to display either (i) low spatial-frequency information only (low-SF training group; blurring to remove superficial information); (ii) high spatial-frequency information only (high-SF training group; an ‘edge detector’ to highlight superficial information); or (iii) normal vision (normal-SF group). Participants were asked to anticipate the direction of the shuttle when footage was occluded at the moment of racquet-shuttle contact. In the post-test, response accuracy when viewing deceptive trials was higher for the low-SF training group when compared to the normal-SF (control) training group (p = .005), with the difference retained in the retention test (p = .020). High-SF training resulted in greater performance at post-test (p = .038) but not retention (p = .956). The analysis of gaze provided some explanation for the findings, with the low-SF training group spending more time after training fixating on the location of racquet-shuttle contact than did the normal training group (p = .028). The findings demonstrate that training which conveys only the basic kinematic movements visible in low-SF information may be effective in learning to ‘see-through’ deceptive intent.